2021
DOI: 10.1007/s10750-020-04488-4
|View full text |Cite
|
Sign up to set email alerts
|

Environmental nitrate impacts foraging and agonistic behaviours of invasive non-native crayfish (Pacifastacus leniusculus and Faxonius virilis)

Abstract: Life history traits such as predation and foraging are key behavioural mechanisms through which invasive, non-native species can have a detrimental effect on the resident flora and fauna of recipient ecosystems. Environmental change may alter these traits in ways that are currently poorly understood. In aquatic ecosystems, changes to the environment such as nitrate pollution can have chronic, unforeseen consequences for both native and invasive species. As keystone species and ecosystem engineers, non-native c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Verdcourt); however, these effects were complex and confounded by depth and frequency of water level fluctuations (Zhang et al, 2021). Another study showed that increased nitrate concentrations decreased agonistic interactions between two invasive crayfish species and reduced their foraging efficiency, which is likely to have complex effects on invasion dynamics (James et al, 2021). Harmful algal blooms (HABs), increasing in frequency with eutrophication, can also shift the balance between invasive and native species as well as between the different invasive species, depending on their tolerance.…”
Section: Impacts Of Aismentioning
confidence: 99%
“…Verdcourt); however, these effects were complex and confounded by depth and frequency of water level fluctuations (Zhang et al, 2021). Another study showed that increased nitrate concentrations decreased agonistic interactions between two invasive crayfish species and reduced their foraging efficiency, which is likely to have complex effects on invasion dynamics (James et al, 2021). Harmful algal blooms (HABs), increasing in frequency with eutrophication, can also shift the balance between invasive and native species as well as between the different invasive species, depending on their tolerance.…”
Section: Impacts Of Aismentioning
confidence: 99%